The evaluation of sequential platelet counts has prognostic value for acute kidney injury patients requiring dialysis in the intensive care setting (Clinics, 2013)
OBJECTIVE: To evaluate the prognostic value of platelet counts in acute kidney injury patients requiring renal replacement therapy. METHODS: This prospective cohort study was performed in three tertiary-care hospitals. Platelet counts were obtained upon admission to the intensive care unit and during the first week of renal replacement therapy on days 1, 3, 5 and 7. The outcome of interest was the hospital mortality rate. With the aim of minimizing individual variation, we analyzed the relative platelet counts on days 3, 5, 7 and at the point of the largest variation during the first week of renal replacement therapy. Logistic regression analysis was used to test the prognostic value of the platelet counts. RESULTS: The study included 274 patients. The hospital mortality rate was 62%. The survivors had significantly higher platelet counts upon admission to the intensive care unit compared to the non-survivors [175.5×103/mm3 (108.5-259×103/mm3) vs. 148×103/mm3 (80−141×103/mm3)] and during the first week of renal replacement therapy. The relative platelet count reductions were significantly associated with a higher hospital mortality rate compared with the platelet count increases (70% vs. 44% at the nadir, respectively). A relative platelet count reduction >;60% was significantly associated with a worse outcome (mortality rate = 82.6%). Relative platelet count variations and the percentage of reduction were independent risk factors of hospital mortality during the first week of renal replacement therapy. CONCLUSION: Platelet counts upon admission to the intensive care unit and at the beginning of renal replacement therapy as well as sequential platelet count evaluation have prognostic value in acute kidney injury patients requiring renal replacement therapy.